Experimental analysis on the formation of CO-NO-HC in swirling flow combustion chamber - Ashrul Ishak, Mohamad Shaiful (Penerbit UTM Press, 2014)
The main purpose of this paper is to evaluate the production of CO-NO-HC emissions while varying the swirl angle of curve vane radial swirler. Swirling flow generates central recirculation region (CRZ) which is necessary for flame stability and enhances fuel air mixing. Therefore designing an appropriate air swirler is a challenge to produce stable, efficient and low emission combustion inside burner system. Four radial curved vane swirlers with 30o, 40o, 50o and 60o vane angles corresponding to swirl numbers of 0.366, 0.630, 0.978 and 1.427 respectively were used in this experiment to measure the vane angles effect on emission production in the combustion chamber. Emission measurements were conducted at 5 axial distances from the burner throat, and at 5 locations along the radius starting the central axis at each section. It was found that at the core near the throat, CO and HC concentrations are low due to high available O2 and high fuel mixing rate producing efficient combustion. This is due to the high shear region created the high swirl flow.